ANALISIS GAYA BAHASA PADA PUISI MENYESAL KARYA ALI HASJMI - Ateng Wahyudi; Rochmat Tri Sudrajat; Reka Yuda Mahardika (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Poetry is a literary work whose language is bound by rhyme and is a person's ideas and feelings about something that are poured into beautiful words.  Language style is one of the media in stylistic studies that can be used as a medium in assessing the beauty of fictional poetry and prose works.  The background of this research is to analyze the language style (figure of speech) used in Ali Hasjmi's sorry poetry, as well as to assist in the development of Indonesian language learning in analyzing the language style of the poetry.  The method used by researchers is a qualitative descriptive method.  The data analysis was carried out through several stages including literature study by reading, writing the required content, and identifying the verse and lines of poetry that contained language styles.  The results found in Ali Hasjmi's regretful poetry include three styles of language including affirmation, satire and comparison.  The figures used are personification, metaphoric, hyperbole, sinekdoke, rhetorical, and irony.  In regret poetry there are four stanzas and fifteen lines.